Management of severe hyponatremia in a chronic kidney disease patient; a case report - Anass Qasem; Syed Arman Rabbani; Martin Thomas Kurian; Sathvik B Sridhar (Journal of Nephropharmacology)
Hyponatremia is a common electrolyte abnormality in chronic kidney disease (CKD). Managing severe hyponatremia in CKD is challenging, requiring the correction of biochemical imbalances and fluid overload, often through traditional hemodialysis. However, this can lead to rapid serum sodium correction, potentially causing neurological complications. We present a case of a CKD patient with a suspected stroke, who exhibited dizziness, confusion, and an unsteady gait, and was found to have azotemia, metabolic acidosis, and severe hyponatremia (101 mmol/L). We managed the case by gradually correcting the serum sodium with hypertonic saline. Subsequently, we initiated traditional hemodialysis using a dialysate sodium concentration of 130 mEq/L when the serum sodium levels increased to 122 mmol/L. The patient was discharged in a vitally and hemodynamically stable condition, with a serum sodium level of 137 mmol/L. This report highlights the intricacies of managing severe hyponatremia in a CKD patient with a suspected stroke.